Islamic Religious Education Teachers' Efforts to Overcome Students' Academic Anxiety Through an Islamic Approach - Siska Nur Jannah; Lailatul Fitriyah (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
This research is motivated by the increasing phenomenon of academic anxiety experienced by junior high school students, such as fear of exams, lack of confidence during presentations, and pressure in completing academic assignments. These conditions can affect students' concentration, motivation, and academic results, so an approach that can touch the psychological and spiritual aspects of students is needed. This study aims to describe the forms of academic anxiety in students and analyze the efforts of Islamic Religious Education (PAI) teachers in overcoming academic anxiety through an Islamic approach. The study used a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation studies. Research informants included the principal, PAI teachers, and ninth-grade students. The results showed that students' academic anxiety appears in the form of nervousness, fear of failure, lack of confidence, and physical symptoms such as trembling hands and feelings of restlessness when facing exams or presentations. PAI teachers play an important role in overcoming these conditions through an Islamic approach that is manifested in the habit of praying before learning, reading the Qur'an, providing motivation, religious advice, and instilling the values ​​of tawakal (religious trust), patience, and ikhtirah (independence). This approach can create a more comfortable learning atmosphere, increase students' emotional calm, and help students become more confident in facing academic demands. This study shows that the Islamic approach has a positive contribution in supporting mental health and character formation of students in the school environment.